2017
DOI: 10.31529/sjms.2017.3.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Job Turnover: A Case Study of Private Schools of District Swat

Abstract: Several factors force employees to leave the organization.This study examines the relationship among job turnover intention, workload, low pay and job stress in private schools at district swat. For this purpose, the data has been collected from of two hundred and forty eight employees. The results of the study indicated that workload, low pay and job stress are significantly positive related to turnover intention. This study also suggested that for overcoming the turnover from the schools enough salary should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This result is difference from the previous studies that emphasized salary. Research by (Loeb et al, 2005;Shah & Jumani, 2015;Weldeyohannes, 2016;Kahn et al, 2017) concluded that teacher turnover intentions were mainly due to salaries.…”
Section: Reward Affect Directly Negative On Turnover Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is difference from the previous studies that emphasized salary. Research by (Loeb et al, 2005;Shah & Jumani, 2015;Weldeyohannes, 2016;Kahn et al, 2017) concluded that teacher turnover intentions were mainly due to salaries.…”
Section: Reward Affect Directly Negative On Turnover Intentionmentioning
confidence: 99%
“…Many previous researchers have examined the teacher's turnover intention. Some of the research were conducted by (Loeb, Darling-Hammond, & Luczak, 2005;Janik & Rothmann, 2015;Shah & Jumani, 2015;Chika, Irene, Joseph, & Ayooluwa, 2016;Jaswani, 2016;Heikonena, Pietarinenb, Kirsi Pyhältöc, Toome, & Soinif, 2016;Larkin, Brantley-Dias, & Lokey-Vega, 2016;Kahn & Qadir, 2016;Tiplic, Lejonberg, & Elstad, 2016;Weldeyohannes, 2016;Ajayi & Olatunji, 2017;Kahn, Mateen, Hussain, Sohail, & Kahn, 2017;Chalim, 2018;Yang, Fan, Chen, Hsu, & Chien, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Very fast changes in financial conditions and expansion in innovation has made many issues like rivalry between employees and organizations. Organizations wants their employees to work more smartly in competition and resulting job stress and low pay (Khan, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research results from Qureshi et al (2013), Yang et al (2014, Khan et al (2014), and Pradana and Salehudin (2015) prove that workload affects the turnover intention. The workload is closely related to feeling tired when given excessively to employees and this can trigger a turnover of the employee (Bakker et al, 2008).…”
Section: Hypothesis Development the Hypothesis Of This Research Ismentioning
confidence: 97%